(untitled) (Religious dialogue and cooperation, 2021)
According to the percentage of Muslims in the total population of the country, North Macedonia is on the third place in Europe. With about one third of the entire population being Muslim, our country is right after Albania and Bosnia and Hercegovina. Islam is an Abrahamic monotheistic universal religion and the second largest religion in the world. The followers of this religion are called Muslims. Muslims believe that God gave his divine word in the form of revelations through various prophets and that Muhammad was the last of God’s Messengers. Every religion has its own religious traditions and customs that have existed for centuries. Certain sacred practices and rituals are very important to Muslims. They are a significant way that enables followers of Islam to remember history, express conviction, and grow in devotion. Some rituals are practiced daily, like prayer; others are practiced annually, like those aligned with specific Islamic holidays. The Five Pillars of Islam are five practices regarded by all sects of the Islamic religion as essential to the Muslim faith. Although there are important differences between Christianity and Islam regarding traditions, customs and cultural heritage. However, in both religions, due to the secularism in our country, the impression is that religion diminishes its meaning in everyday life. Young people adapt to the contemporary way of life that brings great changes in the practice of religious rituals and practices. This paper is about religious rituals and customs as religious elements and their meaning for Muslim families in Macedonia. The paper aims to determine whether and how often Islamic rituals and practices are practiced. Specifically, does their practicing reduce the importance for Muslim families? For the purposes of this paper, a quantitative survey of 60 Muslim religious subjects’ wаs conducted to answer questions related to their views on religion and its practice.